Anti-pancreatic lipase and anti-adipogenic effects of 5,7,3′,4′,5′-pentamethoxy and 6,2′,4′-trimethoxy flavone - An in vitro study - Bilal, Ahmad; Emily P., Friar; Emerald, Taylor; Muhammad Sufyan, Vohra; Christopher J., Serpell; Michelle D., Garrett; Jason Siau Ee, Loo; Isabel Lim, Fong; Eng Hwa, Wong (Elsevier Science Direct, 2023)
In this study, the anti-obesity effects of 5,7,3′,4′,5′ -pentamethoxyflavone (PMF) and 6,2′,4′-trimethoxyflavone (TMF) were evaluated through two distinct mechanisms of action: inhibition of crude porcine pancreatic lipase(PL), and inhibition of adipogenesis in 3T3-L1 pre-adipocytes. Both flavones show dose dependent, competitive inhibition of PL activity. Molecular docking studies revealed binding of the flavones to the active site of PL. In 3T3-L1 adipocytes, both flavones reduced the accumulation of lipids and triglycerides. PMF and TMF also lowered the expression of adipogenic and lipogenic genes. They both reduced the expression of peroxisome proliferator-activated receptor-gamma (PPAR-γ), CCAAT/enhancer-binding protein α and β (C/EBP α and β), sterol regulatory element-binding protein 1 (SREBF 1), fatty acid synthase (FASN), adipocyte binding protein 2(aP2), and leptin gene. In addition, these flavones enhanced adiponectin mRNA expression, increased lipolysis and enhanced the expression of lipolytic genes: adipose triglycerides lipase (ATGL), hormone sensitive lipase (HSL) and monoglycerides lipase (MAGL) in mature 3T3-L1 adipocytes. Overall, PMF was seen to be a more potent inhibitor of both PL activity and adipogenesis versus TMF. These results suggest that PMF and TMF possess anti-obesity activities and can be further evaluated for their anti-obesity effects.